Financial Market Integration in a Monetary Union - Claudia M. Buch (Kiel Institute of World Economics (IfW), 2001)
Financial markets in Euroland differ from those of a national monetary union in two regards. First, capital markets in general and banking markets in particular show a greater degree of segmentation than national financial markets as a result of information costs and regulatory barriers to full integration. Second, financial market structures differ among the members of Euroland, which potentially affects the transmission of (monetary) shocks. This paper provides a simple model of a currency union which takes these peculiarities into account, focusing on the interaction of financial structures, the degree of capital mobility, the transmission of shocks, and the portfolio choices of banks.
Keywords: F36; 330; monetary union; capital mobility; financial structures; transmission channels; commercial banking; Finanzmarkt; Bank; Marktintegration; Internationale Kapitalmobilität; Währungsunion; Europäische Wirtschafts- und Währungsunion; Finanzintermediär; Internationale Kreditvergabe; Portfolio-Management; Kapitalstruktur